Papua New Guinea Economic Update, September 2022 : Benefiting From High Commodity Prices - World Bank (Washington, DC, 2022)
The Special Focus for this issue is on long-term growth, emphasizing the challenges PNG is facing. The chapter identifies the underlying challenges of low and volatile growth in the country and aims at starting a public discussion to better understand the problems and, thus, contribute to finding solutions. The modest headline economic growth in PNG has translated into meager per capita income growth in the past four decades. While the economy expanded by 3.2 percent on average during 1980-2021, per capita GDP recorded an average annual growth rate of only 0.9 percent. The gap in per capita income level compared to peer countries has typically widened. Despite being at a similar level of development in the 1970s and some progress gained in the early 1990s, PNG’s income level is diverging away from the EAP region. This calls for a renewed policy focus on boosting economic growth. A new growth strategy would need to address the three interrelated growth challenges that the economy is facing: (i) excessive macroeconomic volatility; (ii) low productivity growth; and (iii) excessive reliance on natural capital and not enough on human and institutional capital.